(untitled) (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Extra-marital relationship is a dangerous social disease. Today Bangladesh is fraught with the infection of this disease. The curse of adultery does not stop only upon the killing, suicide or sacrifice of men and women, but the society undergoes the heavily poisonous load of this disease. Under the banner of extramarital affairs, illegal physical relationship is corrupting our society today, and tearing apart the societal and familial ties. Proper implementation of God-given Islamic Law may exonerate the society from this disorder. This article, in the light of the Qur'an and Sunnah, has tried to argue that Islamic Law may play the proper and effective role in freeing the nation from the black clutches of the extra-marital affairs. By comparing the existing laws of the Penal Code of Bangladesh with Islamic Law, an attempt has been made to explore the supremacy of the concerned Islamic law over its Bangladeshi counterpart while highlighting the loopholes of the latter. In terms of Islamic law, the references have been brought from the Quran and Sunnah, and in terms of the existing laws, Penal Code 1960 and Nari o Shishu Nirjatan Daman Ain 2000 have been cited. Newspaper citations and survey methods have been used where necessary. This article has proved that the existing law has stood useless in curbing the crime like the extra-marital affairs. In this case, if Islamic penal laws are implemented, the crime of extra-marital affairs would be eradicated, family peace would be restored, and ideal society would be established. সারসংক্ষেপ : পরকীয়া একটি ভয়াবহ সামাজিক ব্যাধি। বাংলাদেশ আজ এই ব্যাধির সংক্রমণে জর্জরিত। পরকীয়ার অভিশাপে নারী-পুরুষের হত্যা, আত্মহত্যা বা বলিদানেই শেষ হয় না; বরং তার বিষক্রিয়ায় ক্ষতিগ্রস্ত হচ্ছে সমাজ। পরকীয়া প্রেমের নামে অবৈধ দৈহিক সম্পর্ক আজ আমাদের সমাজকে করেছে কলুষিত, ভেঙ্গে দিচ্ছে সমাজ ও পারিবারিক শৃঙ্খলা। আল্লাহ প্রদত্ত ইসলামী আইনের যথাযথ বাস্তবায়ন এই ব্যাধি থেকে সমাজকে মুক্ত করতে পারে। আলোচ্য প্রবন্ধে কুরআন-সুন্নাহ্র আলোকে প্রমাণ করার চেষ্টা করা হয়েছে যে, পরকীয়ার কালো থাবা থেকে জাতিকে মুক্ত করার ক্ষেত্রে ইসলামী আইন যথাযথ ও কার্যকর ভূমিকা রাখে। বাংলাদেশে প্রচলিত দ-বিধিকে ইসলামী আইনের সঙ্গে তুলনা করে প্রচলিত আইনের দুর্বল দিকগুলো পর্যালোচনাপূর্বক ইসলামী আইনের শ্রেষ্ঠত্ব তুলে ধরার প্রয়াস চালানো হয়েছে। ইসলামী আইনের ক্ষেত্রে কুরআন-সুন্নাহ থেকে এবং প্রচলিত আইনের ক্ষেত্রে চবহধষ পড়ফব-১৮৬০ ও নারী ও শিশু নির্যাতন দমন আইন ২০০০ থেকে উদ্ধৃতি প্রদান করা হয়েছে। প্রযোজ্য ক্ষেত্রে সংবাদপত্রের উদ্ধৃতি ও সমীক্ষা পদ্ধতির আশ্রয় নেয়া হয়েছে। এ প্রবন্ধ থেকে প্রমাণিত হয়েছে যে, প্রচলিত আইন পরকীয়ার মতো জঘন্য অপরাধ দমনে ব্যর্থতার পরিচয় দিয়েছে। এ ক্ষেত্রে ইসলামী হদ্দ তথা দণ্ডবিধি অনুসরণ করা হলে নির্মূল হবে পরকীয়া, প্রতিষ্ঠা হবে পারিবারিক শান্তি, গড়ে উঠবে আদর্শ সমাজ।